(untitled) (American Journal of Management, 2022)
Based on behavioral entrepreneurship and institutional theory, we build a conceptual framework that describes the nature of the relationship between startup rates and economic growth. Our model indicates that the effects of startup rates on economic growth are contingent on entrepreneurship quality that is characterized by innovativeness, high growth, and export orientation. Then we investigate what factors determine the quality of entrepreneurship. We presuppose that entrepreneurial behaviors including entrepreneurial motivation, opportunity recognition, and resource construction are crucial antecedents of entrepreneurship quality. The linkages between entrepreneurial behaviors and entrepreneurship quality are positively moderated by environment factors according to institutional theory. These macro factors include economic freedom, policy supportiveness, cultural openness, and social supportiveness. We draw implications for research as well as the policy community.